Cuidado às crianças/adolescentes com necessidades especiais de saúde na atenção domiciliar: percepção da família - Lima, Paloma Mayara Vieira de Macena (2022)
Introduction: Children and adolescents with special health needs in home care require comprehensive and continuous assistance from their relatives, which becomes more satisfactory with the support of trained health professionals. Objective: To understand the family’s perception about the care provided by home care services to children and adolescents with special health needs. Method: Qualitative, descriptive and exploratory research, carried out with 15 relatives of children with special health needs who receive assistance from Home Care Services in nine cities in the state of Paraíba. The interviews took place through telephone calls between June and September 2021, were recorded by digital applications, transcribed and interpreted by Inductive Thematic Analysis. The project was approved by the Research Ethics Committee, under CAAE: 45615521.8.0000.5188 and Protocol nº: 4.736.299. Results: For relatives of children/adolescents with special health needs, the Home Care Service provides fundamental care for the consolidation of comprehensive assistance, making available therapeutic care, management of health devices, medicines, supplies, referrals to specialists and guidelines for their care. It should be highlighted the presence of attentive professionals and the articulation of complementary actions and services of the Health Care Network that seek to solve their health demands. The vulnerabilities of families and children/adolescents are evident, due to weaknesses in the network and in the home service of some cities, such as inconsistencies in the services and the lack of accountability of both primary care for the care of this public and the municipal management in establishing the appropriate governance system in the health network. Conclusion: The care provided to children/adolescents with special health needs by Home Care Services has proven to be effective, and it becomes essential in supporting the family, as it allows for the continuity of care. It is essential to have a close look from managers to solve the disarticulation of these services in the network. With this study, health professionals have subsidies to improve their home care actions.